2015
DOI: 10.1158/1535-7163.mct-15-0201-t
|View full text |Cite
|
Sign up to set email alerts
|

Gene Knockdown by EpCAM Aptamer–siRNA Chimeras Suppresses Epithelial Breast Cancers and Their Tumor-Initiating Cells

Abstract: Effective therapeutic strategies for in vivo siRNA delivery to knockdown genes in cells outside the liver are needed to harness RNA interference for treating cancer. EpCAM is a tumor-associated antigen highly expressed on common epithelial cancers and their tumor-initiating cells (TIC, also known as cancer stem cells

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 48 publications
(70 reference statements)
1
44
0
Order By: Relevance
“…Thus, this tool could also be used to study the role of host genes in SIV transmission in macaques, where gene knockout is not easy. We have recently found that EpCAM-AsiCs given subcutaneously can silence gene expression in EpCAM+ cells distributed at distal sites throughout the mouse (Gilboa-Geffen et al, 2015). Preliminary studies of subcutaneous injection of CD4-AsiCs in humanized mice also show strong knockdown (~80%) in CD4+ T cells in local lymph nodes, as well as in the spleen and distal lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this tool could also be used to study the role of host genes in SIV transmission in macaques, where gene knockout is not easy. We have recently found that EpCAM-AsiCs given subcutaneously can silence gene expression in EpCAM+ cells distributed at distal sites throughout the mouse (Gilboa-Geffen et al, 2015). Preliminary studies of subcutaneous injection of CD4-AsiCs in humanized mice also show strong knockdown (~80%) in CD4+ T cells in local lymph nodes, as well as in the spleen and distal lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…These are taken up by receptor-mediated endocytosis and cleaved by Dicer to liberate an active siRNA. Recent work with breast cancer homing epithelial cell adhesion molecule (EpCAM) aptamer–siRNA chimaeras suggests that, like GalNAc conjugates, they concentrate in targeted tissues after subcutaneous injection 95 . Application of improved chemistries for nuclease stability and novel endosomal escape strategies may further improve this versatile siRNA delivery platform.…”
Section: Moving Beyond the Livermentioning
confidence: 99%
“…We recently found that subcutaneous administration of naked aptamer-siRNAs (AsiCs) targeting CD4 or an epithelial cancer receptor concentrate in aptamer-targeted cells, leading to systemic gene knockdown (i.e., the CD4-AsiC causes efficient knockdown in the spleen and distal lymph nodes) [49] (and J.L., unpublished). Subcutaneous administration of aptamers and aptamer conjugates should provide a good solution to the poor pharmacological properties of intravenously injected small RNAs, enabling aptamers to substitute for antibodies in many in vivo applications.…”
Section: Aptamers Vs Antibodiesmentioning
confidence: 99%